DYNAMICS OF LEADERSHIP AND POWER - Dwi Nur'aeni, Dita (Journal Education and Government Wiyata, 2023)
Leadership dynamics is a process of change in the relationship between leaders and followers in achieving organizational goals. Influenced by factors such as human relations, leadership styles, and organizational change, these dynamics involve interactions within leadership roles. Closely related to leadership, the leader's power is used to achieve organizational goals, with the distribution of power being a key element. Legitimacy in power is important, and leaders must have a basis of widespread acceptance. In the distribution of power, leaders have a significant role, influencing whether power is centralized or evenly distributed. Leadership style, as a leader's pattern of action, influences leadership and power dynamics. Leadership style reflects the combination of philosophy, skills, traits, and attitudes that underlie behavior, and influences the extent to which power is used and recognized by group members. Overall, the complex relationship between leadership style and power dynamics has significant implications for social and political developments, especially in Indonesia. Choosing a leadership style that suits the values and needs of society is the key to advancing sustainable and inclusive development. Understanding these relationships helps develop balanced and effective leadership and power structures in accordance with the values held by the organization or society.